A review on accessible techniques for removal of hexavalent Chromium and divalent Nickel from industrial wastewater: Recent research and future outlook. (1st May 2021) - Kumar, Vinay; Dwivedi, S.K.
Abstract: The present era is seeking our attention on the dilemma caused by the contamination of the aquatic system with chromium (Cr) and nickel (Ni). Amid Ni and Cr oxidation states, hexavalent Cr (Cr(VI)) and divalent Ni (Ni(II)) often found in the contaminated water body with prominent toxicity on flora and fauna. The negative consequences of the Cr and Ni are strongly connected with human health. The effluents discharged by ventures such as plating, tannery, battery, mining, coloring, material, paint, metal processing etc. industries also bring Cr and Ni into the water body. The removal of Cr and Ni from waste/industrial water faced the difficulties owing to inappropriate selection of technologies in aspects of cost, technique, efficiency and sustainability. Thus, in this review we discussed the chemistry and toxicity of Cr(VI) and Ni(II) and have bring together all the possible methods that can be effectively exploited for the treatment of Cr(VI) and Ni(II) contaminated water. We have also focused on the recent advances in integration/combination of biological or natural processes with other existing methods that have high scope for future research and have great opportunity in treatment of Cr and Ni contaminated water in ecofriendly and sustainable way in upcoming days. Highlights: Cr(VI) and Ni(II) causes toxicity and mutagenicity in humans and plants. Cr(VI) and Ni(II) water contamination arises from various sources. Accessible methods for treatment of Cr(VI)/Ni(II) contaminated wastewater has been reviewed. Bio-Integrated techniques possibly more efficient for ecofriendly treatment of Cr/Ni contaminated wastewater.